Aryldiazonium ion initiated C–N bond cleavage for the versatile, efficient and regioselective ring opening of aziridines. Issue 11 (12th April 2019) - Zhang, Xiulian; Qiu, Xianfan; Rong, Jing; Su, Zhenni; Cui, Xin; Tao, Chuanzhou
Abstract : Aryldiazonium salts have been proved to initiate the regioselective cleavage of aziridines for the installation of varied functional groups. Abstract : Aryldiazonium salts have been proved to initiate the regioselective cleavage of aziridines for the installation of varied functional groups. The ring-opening process is effective and general for a variety of nucleophiles, including [O], [S] and [N], at room temperature. This highly regioselective process, which can be performed at the gram scale, enjoys operational simplicity, as well as mild and metal-free conditions. The postulated reaction mechanism involves a single electron transfer from aziridines to aryldiazonium salts, which generates a highly reactive amino radical cation.